Sounding the Color Line : Music and Race in the Southern Imagination - Nunn, Erich (Book collections on Project MUSE., 2015)
Sounding the Color Line explores how competing understandings of the U.S. South in the first decades of the twentieth century have led us to experience musical forms, sounds, and genres in racialized contexts. Yet, though we may speak of white or black music, rock or rap, sounds constantly leak through such barriers. A critical disjuncture exists, then, between actual interracial musical and cultural forms on the one hand and racialized structures of feeling on the other. This is nowhere more apparent than in the South. Like Jim Crow segregation, the separation of musical forms along racial li.